Trust and leadership styles in Ecuador: Divergent perspective by managers and subordinates - Espinoza-Solís, Eduardo; Elgoibar, Patricia (Opción, 2020)
The present study aimed to analyze empirically the relationship between cognitive andaffective trust and the leadership styles of managers and subordinates. Two samples werecollected: the perception of the managers (N=341) and of the employees (N=314). Thehypotheses were tested through a structural equation (SEM). Results showed that from themanagerial perspective, cognitive and affective trust and leadership styles were significantlyand positively correlated to a different extent. In addition, cognitive trust was found tomediate the relationship between leadership styles and affective trust. In contrast, theemployees’ perspective showed no correlation between the aforementioned variables.Finally, theoretical and practical implications and suggestions for future research wereproposed.Resumen El presente estudio pretende analizar, de manera empírica, la relación entre confianza cognitiva y afectiva con los estilos de liderazgo de los administradores y subordinados. Para ello, dos muestras fueron recolectadas: una con la percepción de los administradores (N=341) y otra con la de los empleados (N=314). Las hipótesis fueron contrastadas a través de ecuaciones estructurales (SEM). Los resultados demuestran que bajo la perspectiva de los administradores los tipos de confianza y estilos de liderazgo presentan una significativa y positiva correlación. Además, la confianza cognitiva ejerce una mediación entre los estilos de liderazgo y la confianza afectiva. En contraste, bajo la perspectiva de los subordinados no existe relación entre estas variables del comportamiento organizacional. Finalmente se presentan implicaciones teóricas y prácticas, así como sugerencias para futuras investigaciones